Biblical Motives in the Legend on Flood in the Mythology of the North-West Native Americans - SIKHARULIDZE, Ketevan (Journal in Humanities, 2013)
The article covers the theme of flood which is found in the American folklore, namely, in the mythology of the Indians living on the northwestcoast.The text "Mount Rainier" is provided as an example. Myths on flood are based on traditional folkloric motives and images ofIndians. At the same time, the trace of influence of the biblical story of Noah is noticed in some texts.Appearance of biblical story elements in the text of Indians can not be attributed to the old epoch, since these peoples did not make acultural unity in the past. This process must have begun after settlement of Europens on the American Continent, especially after activationof missionaries.